Penerapan model pembelajaran cooperative integrated reading and composition (circ) untuk meningkatkan kemampuan membaca pemahaman pada peserta didik kelas V di sekolah dasar - Yulia Shinta Dewi; St. Y. Slamet; Sukarno Sukarno (Universitas Sebelas Maret, 2025)
The study aims to describe the application of Cooperative Integrated Reading and Composition learning model on reading comprehension skills of grade V students at SDN Tegalsari, explain the obstacles and solutions, and describe the results of improving reading comprehension skills. This research is a class action research referring to the Kemmis and Taggart model. The research subjects were the fifth grade teacher and 11 students. Data collection techniques were non-test and test. Data analysis uses qualitative and descriptive quantitative. The results of this study are as follows. The application of the Cooperative Integrated Reading and Composition learning model can improve reading comprehension skills, the obstacles faced are that students are less active, students do not dare to ask or answer questions, and there is one group member who does not participate in the discussion. The solution to overcome these obstacles is that the teacher asks students to read the text, the teacher stimulates students to ask or answer questions and approaches students to follow the discussion. The improvement of reading comprehension skills in terms of scores has increased from cycle I by 54% and cycle II to 72%.